Strategi Optimalisasi Pembiayaan Murabahah dalam Meningkatkan Pendapatan Margin pada Koperasi Syari'ah - Dinitha Indriyani Hasbi Maula; Heri Nugraha; Nurjamil Nurjamil (LPPM Universitas Koperasi Indonesia, 2026)
Murabahah financing is one of the financing products that serves as the main source of margin income for Islamic cooperatives. However, an increase in the amount of financing disbursed is not always followed by an optimal increase in margin income. Therefore, an optimization strategy for murabahah financing is needed to enhance margin income and support the sustainability of cooperative operations. This study is motivated by the importance of effective and efficient management of murabahah financing at Koperasi Syari'ah Baitul Muttaqin, Bandung City. This study aims to analyze the optimization strategy of murabahah financing in increasing margin income at Koperasi Syari'ah Baitul Muttaqin, Bandung City. This study employed a qualitative method with a case study approach. Data were collected through observation, interviews, and documentation involving managers, financing staff, andmembers receiving murabahah financing. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The results indicate that the optimization strategy for murabahah financing is implemented through selective financing feasibility analysis, mutually agreed margin determination, improvement of service quality for members, and monitoring and supervision of the financing that has been disbursed. These strategies contribute to smoother installment payments, minimize the risk of non-performing financing, and support the increase in murabahah financing margin income. In conclusion, the optimization of murabahah financing through the implementation of sound financing management is able to increase margin income at Koperasi Syari'ah Baitul Muttaqin, Bandung City. Nevertheless, continuous efforts are still required to improve the effectiveness of financingmanagement and maintain the quality of the financing provided.